A new species of Amazophrynella (Anura: Bufonidae) from southern Amazonia - Avila, Robson W.; Carvalho, Vinicius T.; Gordo, Marcelo; Kawashita-Ribeiro, Ricardo A.; Morais, Drausio H. [UNESP] (Magnolia Press, 2012)
A new species of the genus Amazophrynella is described from southern Amazonia, Brazil. The new species is characterized by its medium size for the genus (15.2-19.3 mm SVL in males, 20.2-25.7 mm SVL in females), snout rounded in dorsal view, acute in lateral view, presence of subrostral crest not converging anteriorly, finger I shorter than finger II, and by dorsal and ventral coloration. The reproductive behavior of the new species is similar to other Amazophrynella with pigmented and numerous eggs that are probably laid in temporary ponds.
Keywords: Amphibia; Bufonidae; Anura; Amazon